THE IDEOLOGICAL FOUNDATIONS OF THE US CONSTITUTION OF 1787 AS THE BASIS FOR THE STABILITY OF THE SOCIO-POLITICAL SYSTEM OF AMERICAN STATE (Law and Safety, 2018)
The object of the article is an ideological representation of the socio-political system of the United States in the XVIII century pf the representatives of two most influential movements of those times, Republicans and Federalists, which were laid down in the Constitution of the United States in 1787.The objective of the article is to highlight the state of political and legal thinking in the United States during the struggle for independence and its impact on the constitutional process; the identification of those aspects that are universal; and the definition of ideological foundations that can positively influence the state-building processes in Ukraine.The relevance of the study is to clarify theoretical heritage of the past, which was laid in the basis of one of the leader-states of the state and legal development of the USA, since this experience can be useful in Ukraine.During the study, the author came to the conclusion that the strong components of the US Constitution of 1787 were: the skillful use of American political thought of the late XVIII century to socio-economic realities; the possibility of reaching a political compromise in terms of the acute ideological struggle of the Republicans and Federalists; successful structure of the Constitution; “strict order” for making amendments and alterations to the Constitution; the implementation of the institutions of constitutional interpretation and control.